The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.48550/arxiv.2103.08565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nature of the ferromagnetic-antiferromagnetic transition in Y$_{1-x}$La$_{x}$TiO$_{3}$

S. Hameed,
S. El-Khatib,
K. P. Olson
et al.

Abstract: We explore the magnetically-ordered ground state of the isovalently-substituted Mott-insulator Y1−xLaxTiO3 for x ≤ 0.3 via single crystal growth, magnetometry, neutron diffraction, x-ray magnetic circular dichroism (XMCD), muon spin rotation (µSR) and small-angle neutron scattering (SANS). We find that the decrease in the magnetic transition temperature on approaching the ferromagnetic (FM) -antiferromagnetic (AFM) phase boundary at the La concentration xc ≈ 0.3 is accompanied by a strong suppression of both b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…For the growth of Y 1−x La x TiO 3 single crystals, we fixed the value of δ at 0.04, i.e., the same value as for YTiO 3 in order to avoid property changes due to differences in oxygen off-stoichiometry in the starting material composition 8 . Intriguingly, however, we found that, at large x, the changes in T C along the growth axis can be particularly severe.…”
Section: B Characterization Of Y1−xlaxtio3 Single Crystalsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the growth of Y 1−x La x TiO 3 single crystals, we fixed the value of δ at 0.04, i.e., the same value as for YTiO 3 in order to avoid property changes due to differences in oxygen off-stoichiometry in the starting material composition 8 . Intriguingly, however, we found that, at large x, the changes in T C along the growth axis can be particularly severe.…”
Section: B Characterization Of Y1−xlaxtio3 Single Crystalsmentioning
confidence: 99%
“…For our own inelastic neutron measurements of the spin-wave spectra at large La-substitution levels, we used samples from the latter parts of the growths that exhibit a nearly constant T C . Given the strong suppression of the ordered moments exhibited by these samples with La substitution 8 , it was necessary to co-mount samples from many different growths, in order to obtain a sufficiently large signal-to-noise ratio (see Fig. 6) 21 .…”
Section: B Characterization Of Y1−xlaxtio3 Single Crystalsmentioning
confidence: 99%
See 3 more Smart Citations